Peran UMKM Berbasis Perikanan dalam Meningkatkan Kesejahteraan Masyarakat: Studi Kasus CV. Alang-Alang Tumbuh Subur - Krisna Maulana; Muhammad Anas Anas (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the integration of the Wirausaha Merdeka Kampus (WMK) Program in empowering fisheries-based MSMEs, using a case study of CV. Alang-Alang Tumbuh Subur in Boyolali Regency. The program involves collaboration between university students and MSME actors to enhance product innovation, business management, and digital marketing strategies. A qualitative approach was used, with data collected through in-depth interviews, participatory observation, and documentation. The results show that student involvement encourages technology adoption, improves product quality, and expands market networks. Additionally, the role of industry partners such as CV. Alang-Alang is crucial in facilitating knowledge transfer and community-based entrepreneurship practices. Despite challenges regarding program sustainability, this collaboration has proven to significantly contribute to strengthening local MSMEs and providing students with valuable experiential learning opportunities.